Real-time feedback using extended reality: A current overview and further integration into sports - Geisen, M.; Klatt, S. (International Journal of Sports Science & Coaching, 2022)
The learning process in humans is reinforced with feedback on actions. In sports, feedback plays an important role in optimizing motion techniques. Athletes can learn and internalize correct motion executions in order to improve their performance. The most widely used feedback method in sports is response advice by experts (coaches). Meanwhile, technical devices are useful for promoting motor learning. With the help of extended reality, such as virtual reality, augmented reality and mixed reality, it is possible to receive visual feedback through (head-mounted) displays during motion execution for real-time corrections in motor learning. The use of extended reality real-time feedback is becoming increasingly common in many application fields of motor learning. So far, forms of real-time feedback have mainly been used in the health and medical sector. In sports, the increasing exploration of real-time feedback could provide a useful supplement to conventional feedback methods. Real-time feedback using extended reality could enable a better self-motion perception and faster learning success, consequently, having a positive effect on the performance development of athletes. This article summarizes the current use of real-time feedback (Prior application of real-time XR feedback in various research fields section), presents the useful addition of extended reality real-time feedback to common feedback methods in sports (Framework of the addition of real-time XR feedback in sports section), and recommends a possible integration of real-time feedback in sports training with the help of a model (Concept development section). Overall, the benefits of using extended reality technologies are presented, and a human-system-interaction in sports is proposed.